2010
DOI: 10.2903/j.efsa.2010.1817
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the substantiation of health claims related to wheat bran fibre and increase in faecal bulk (ID 3066), reduction in intestinal transit time (ID 828, 839, 3067, 4699) and contribution to the maintenance or achievement of a normal body

Abstract: European Food Safety Authority (EFSA), Parma, Italy SUMMARYFollowing a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies was asked to provide a scientific opinion on a list of health claims pursuant to Article 13 of Regulation (EC) No 1924No /2006. This opinion addresses the scientific substantiation of health claims in relation to wheat bran fibre and increase in faecal bulk, reduction in intestinal transit time and contribution to the maintenance or achievement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…That said, there was an overarching significant increase in perceived stool quantity during fibre the intervention period as compared to during the baseline period (Table 2). The benefits of wheat bran fibre for faecal bulking and transit time are unequivocal, and have been confirmed by EFSA health claim opinions [32]. The present study provides some insight into the concomitant benefits of increasing stool bulk and frequency.…”
Section: Discussionsupporting
confidence: 79%
“…That said, there was an overarching significant increase in perceived stool quantity during fibre the intervention period as compared to during the baseline period (Table 2). The benefits of wheat bran fibre for faecal bulking and transit time are unequivocal, and have been confirmed by EFSA health claim opinions [32]. The present study provides some insight into the concomitant benefits of increasing stool bulk and frequency.…”
Section: Discussionsupporting
confidence: 79%
“…In addition to fiber-related benefits of whole grains, which have been extensively reported [7], research has shown further benefits related to the presence of biologically active compounds and to synergistic effects between dietary fiber and different micronutrients [7,8]. The European Food Safety Authority recommends a dietary fiber intake of 25 g/day, ranging from 10 to 20 g/day in young children and from 16 to 29 g/day in adults [9]. For children, this varies and the general rule for health care professionals is to calculate it as age of child plus 5 (g/day).…”
Section: Introductionmentioning
confidence: 99%
“…So far, the EFSA Panel considered a wide range of specific fibers as sufficiently characterized, and has substantiated a number of the submitted health claims, including wheat bran fiber for a reduction in intestinal transit time and for an increase in fecal bulk [67], rye fiber for contributing to normal bowel function [68], oat and barley grain fiber for an increase in fecal bulk [69], and beta-glucans from oats and barley for a reduction in post-prandial glycemic responses [70], and for maintenance of normal blood cholesterol levels [70,71]. As is apparent from these examples, the EFSA panel is only considering individual products 'as sufficiently characterized'; or combinations of ingredients or products if they are similar regarding the component(s) relevant for the claimed effect (e.g., beta-glucans of oats and barley).…”
Section: Health Claims On Whole-grain Wheat: Status Issues and Perspectivesmentioning
confidence: 99%